Radicalism Prevention through Islamic Religious Education Learning at Elementary School - Nurhayati Nurhayati; Abdul Hamid (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
Radicalism has been a threat to the world civilization and every country has deployed its effort to prevent radicalism especially in the educational sector. Every level of education including elementary school can be designed to prevent radicalism. Given this situation, educators in elementary schools are expected to be able to design and develop the program that are able to prevent students from radicalism understanding. This study was aimed at investigating the efforts of SD (Sekolah Dasar/Elementary School) Putra Kaili Permata Bangsa Palu in preventing radicalism, especially in PAI (Pendidikan Agama Islam/Islamic Religious Education) learning. This research was qualitative using a case study approach. Interview and documentation techniques were used to collect the data. To analyse the data, this study applied Cresswell analysis techniques. The findings of this study show that the school has designed and developed program to prevent radicalism. The efforts deployed by the school included: selecting textbooks, developing learning modules and PAI manuals by teachers, and maintaining nationalism-related activities. The strategy was implemented through PAI learning both in the classroom and outside the classroom. In the classroom learning included the objectives, materials, media, methods, and evaluation of learning process. Outside classroom learning covered extracurricular, religious, and nationalism-related activities.